Improving corrosion resistance of steel rebars in concrete with marble and granite waste dust as partial cement replacement. (10th October 2018) - Ghorbani, Saeid; Taji, Iman; Tavakkolizadeh, Mohmmadreza; Davodi, Ali; de Brito, Jorge
Highlights: Marble and granite dust (MGD) incorporation did not significantly decrease concrete strength. Replacing cement by an adequate MGD content improved corrosion resistance. Using 20% MGD as cement replacement showed higher values of OCP and EIS. Water absorption should not be the only parameter for corrosion assessment in reinforced concrete. Abstract: In this research, the effect of marble and granite waste dust (MGWD) as partial cement replacement (up to 20%) on the mechanical and corrosion behaviour of concrete specimens was investigated. Water cured specimens were kept in a 3.5% by weight of NaCl solution for 92 days. Uniaxial compression and water absorption tests, open circuit potential (OCP), electrochemical impedance spectroscopy (EIS) and Scanning Electron Microscopy (SEM) analysis were conducted. The compressive strength test results showed insignificant negative effect from using MGWD. OCP and EIS measurements revealed that specimens with 20% cement replacement have higher potentials and corrosion resistance than all the others.